Peran Hukum Administrasi Negara dalam Mewujudkan Good Governance di Era Digital - Zen, Najmatul Haya; Frinaldi, Aldi; Roberia, Roberia (Universitas Pahlawan Tuanku Tambusai, 2025)
Governance faces new challenges in the digital era, including misuse of technology and unequal access to information. State Administrative Law (HAN) is crucial in ensuring that digital transformation is in line with the principles of Good Governance. This research aims to analyze the role of HAN in supporting the implementation of Good Governance in the digital era. This research uses a qualitative approach with a descriptive analysis method. The results show that HAN has an important role in realizing Good Governance in the digital era, especially in the aspects of regulation, supervision, and community empowerment. HAN encourages the use of technology to increase efficiency and community involvement, but needs to be balanced with strong regulations to protect community rights. Digitalization can support Good Governance if implemented with a clear legal framework and effective oversight. Optimal implementation of HAN can strengthen public trust and ensure sustainable digital transformation. The government needs to strengthen regulations and supervision related to the application of technology in public administration. Improving people's digital literacy is also important to support participation and oversight of the government.